NEOLIBERAL FRAMEWORK AND TRENDS IN EDUCATION: A FOCUS ON INDIA - Vanisri, Dr. Garimella (IJRDO - Journal of Social Science and Humanities Research, 2018)
Neo-liberal frame work, which emphasizes on free market ideology, has brought in profound transformation and changes in economies worldwide. Alongside free trade and free market, it also affected social dynamics of nations at large particularly, the developing and the under developed. Under the impact of neoliberal frame work, the social policies, individual interests, ideologies, and economic policies are molded in line with its very principles, which eventually led to the retrenchment of governance from welfare activities. In this paper, an attempt has been made to analyse how different nations, particularly India, are dealing with the neoliberal policies of World Bank and IMF, with special focus on how India is coping with the changes in education system. Focus is aslo made on how sometimes these neo liberal policies frame individual and social thoughts. How the post 1990 reforms shaped the middle class thought process in India is also explained. The Information Technology (IT) boom in 1990s tried to construct a meritocracy which promised to liberate the aspiring middle class from citadel of much dis-considered public service system. Employment in IT industries in India needed right full skill with cultural capital (Upadhyay and Vasavi 2006). Cultural capital implies social hierarchies based on class and caste. Always, symbolism is attached to technical education. Technical education at the service of IT is instrumental in distancing middle class from the state; it starts from school education itself. The following story tells how and why IT entered in to India.